(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
CdNi perminvar ferrites doped with Co were prepared through the solid-state reaction using conventional ceramic technique. The compositions of the ferrite were Co0.02Cd0.20Ni0.58Fe2.2O4 and Co0.02Cd0.28Cd0.28Ni0.50Fe2.2O4. X-ray diffraction study of the samples indicates the single phase of perminvar ferrites. Lattice parameter of the samples was found to be 8.3676 and 8.4249 Ã for sample no. (a) of Co0.02Cd0.20Ni0.58Fe2.2O4 and sample no. (b) of Co0.02Cd0.28Ni0.50Fe2.2O4, respectively. The porosity of the samples was found to be 10.03 and 9.53%. The values of Curie temperature for the two samples were found to be 472 Â± 1 and 405 Â± 1Â°C, respectively. Resistivity of the samples was measured from room temperature up to 600Â°C. At 30Â°C resistivity was found to be 334 and 456 ohm-cm, respectively. Frequency dependent dielectric constant for the two samples has been determined from the experimental capacitance values. The value of dielectric constant at frequency, f = 1 kHz and sintering temperature Ts = 1250Â°C was found to be 16.6 Ã 106 and 56.1 Ã 106, for sample no. (a) and (b), respectively. Dielectric constant was observed 3.5 times higher in the Cd rich sample of Co0.02Cd0.28Ni0.50Fe2.2O4 and Co0.02Cd0.20Ni0.58Fe2.2O4. Temperature dependent dielectric constant has been measured for the samples in the temperature range of 30 - 250Â°C. The value of dielectric constant initially increases slowly with increasing temperature and then rises sharply until reaching a certain temperature, then it begins to decrease with further increase of temperature. Anomalies in the resistivity curves have good consistency with the temperature dependent dielectric constant and Curie temperature values. doi: 10.3329/jbas.v32i1.2438 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 23-32, 2008